Simple Ion Transfer at Liquid|Liquid Interfaces - L. J. Sanchez Vallejo; J. M. Ovejero; R. A. Fernández; S. A. Dassie (International Journal of Electrochemistry)
The main aspects related to the charge transfer reactions occurring at the interface between two immiscible electrolyte solutions (ITIES) are described. The particular topics to be discussed involve simple ion transfer. Focus is given on theoretical approaches, numerical simulations, and experimental methodologies. Concerning the theoretical procedures, different computational simulations related to simple ion transfer are reviewed. The main conclusions drawn from the most accepted models are described and analyzed in regard to their relevance for explaining different aspects of ion transfer. We describe numerical simulations implementing different approaches for solving the differential equations associated with the mass transport and charge transfer. These numerical simulations are correlated with selected experimental results; their usefulness in designing new experiments is summarized. Finally, many practical applications can be envisaged regarding the determination of physicochemical properties, electroanalysis, drug lipophilicity, and phase-transfer catalysis.